Loss sensitive investors and positively biased analysts in Hong Kong stock market - Choudhry, Taufiq; Dissanaike, Gishan; Jayasekera, Ranadeva; Kang, Woo-Young; Nnadi, Matthias (Springer, 2021)
The Hong Kong stock market is known to be highly volatile. Professional investors have a strong demand for timely information because of the infrequent nature of Hong Kong analysts’ interim reports (Cheng et al., 2003). Our paper provides a comprehensive study of investor reactions to analysts’ recommendations in the Hong Kong stock market from 2009 to 2014 under different sentiment scenarios. We find that analysts’ recommendation upgrades and downgrades deliver significant information to the Hong Kong stock market. However, analysts’ initiation coverages convey little information and bring about limited impact to the stock market. In addition, analysts’ upgrades and downgrades result in significant differential price impacts in bullish and the bearish phases
Keywords: Analyst recommendation; Hong Kong Stock Exchange; Perception bias; Market sentiment